Cloning and Functional Characterization of Two Germacrene A Oxidases Isolated from Xanthium sibiricum - Dong-Mei Xie; Qiang Zhang; Ling-Kai Xin; Guo-Kai Wang; Cong-Bin Liu; Min-Jian Qin (Molecules, 2022)
Sesquiterpene lactones (STLs) from the cocklebur Xanthium sibiricum exhibit significant anti-tumor activity. Although germacrene A oxidase (GAO), which catalyzes the production of Germacrene A acid (GAA) from germacrene A, an important precursor of germacrene-type STLs, has been reported, the remaining GAOs corresponding to various STLs’ biosynthesis pathways remain unidentified. In this study, 68,199 unigenes were studied in a de novo transcriptome assembly of X. sibiricum fruits. By comparison with previously published GAO sequences, two candidate X. sibiricum GAO gene sequences, XsGAO1 (1467 bp) and XsGAO2 (1527 bp), were identified, cloned, and predicted to encode 488 and 508 amino acids, respectively. Their protein structure, motifs, sequence similarity, and phylogenetic position were similar to those of other GAO proteins. They were most strongly expressed in fruits, according to a quantitative real-time polymerase chain reaction (qRT-PCR), and both XsGAO proteins were localized in the mitochondria of tobacco leaf epidermal cells. The two XsGAO genes were cloned into the expression vector for eukaryotic expression in Saccharomyces cerevisiae, and the enzyme reaction products were detected by gas chromatography–mass spectrometry (GC-MS) and liquid chromatography–mass spectrometry (LC-MS) methods. The results indicated that both XsGAO1 and XsGAO2 catalyzed the two-step conversion of germacrene A (GA) to GAA, meaning they are unlike classical GAO enzymes, which catalyze a three-step conversion of GA to GAA. This cloning and functional study of two GAO genes from X. sibiricum provides a useful basis for further elucidation of the STL biosynthesis pathway in X. sibiricum.